Combined EXAFS spectroscopic and quantum chemical study on the complex formation of Am(III) with formate - Fröhlich, Daniel R.; Koke, Carsten; Panak, Petra (Inorganic chemistry, 2017)
The complexation of Am(III) with formate in aqueous solution is studied as a function of the pH value using a combination of extended X-ray absorption fine structure (EXAFS) spectroscopy, iterative transformation factor analysis (ITFA), and quantum chemical calculations. The Am LIII-edge EXAFS spectra are analyzed to determine the molecular structure (coordination numbers; Am-O and Am-C distances) of the formed Am(III)-formate species and to track the shift of the Am(III) speciation with increasing pH. The experimental data are compared to predictions from density functional calculations. The results indicate that formate binds to Am(III) in a monodentate fashion, in agreement with crystal structures of lanthanide formates. Furthermore, the investigations are complemented by thermodynamic speciation calculations to verify further the results obtained.